Organizations for the Rational Use and Protection of Historical and Cultural Lands - Ganieva, F. S.; S, Rakhmatova S. (European Journal of Life Safety and Stability (2660-9630), 2021)
Today, the use of land around the historic building and structure is a major source of revenue. Efficient use of land is one of the current problems